Designing the Framework for the State Assistance to Provide the Population with Housing - Vidickienė, Dalia; Melnikienė, Rasa (Ekonomika, 1999)
In the course of the overall privatization of the housing stock in Lithuania it was necessary to abandon the mechanism of massive provision of population with the living space from the public funds. The state ownership dominating the housing stock in the period of planned economy backed functioning of such mechanism, and provision of population with the housing stock was one of state’s principle functions. State assistance in providing the population with living space must be adjusted to the needs of market economy, simultaneously integrating this assistance in the country’s overall economic and social policy. One of the methodological alternatives for the design of the system of state assistance in providing the population with housing could be the object-oriented - subject-oriented - subjectivitybased method.The method relies on the analysis of the chosen system in terms of three aspects: 1) Object-oriented; 2) subject-oriented; 3) subjectivist. All the three aspects are considered the most significant parameters, revealing the three-dimensional nature of any socio-economic system. On the basis of the said three aspects, the article proposes the parameters of the system applied in Lithuania by distinguishing them at the levels of self-sufficient, commodity, and financial and credit sections of economy, and treating the subjectivist aspect as preferential.